FAMILY-BASED NURSING EDUCATION TO IMPROVE FAMILY HEALTH LITERACY AND MANAGEMENT FOR STUNTING PREVENTION : A QUASY EXPERIMENTAL STUDY - Nurhafizah Nasution; Ratna Dewi Silalahi (International Archives of Medical Sciences and Public Health, 2026)
Child stunting remains one of the most serious public health challenges worldwide, including in Indonesia. This study evaluated the effectiveness of a Family-Based Nursing (FBN)-based educational programme in improving family health literacy and family management for childhood stunting prevention. A quasi-experimental pre-test–post-test control group study was conducted among 80 families with children aged 0–24 months recruited from two Primary Healthcare Centers in Batam City, Indonesia. The intervention group received a four-week FBN-based educational programme, while the control group received routine health education. The FBN program is more effective at improving health literacy than conventional education, particularly in terms of families’ ability to apply health information to support nutrition, growth monitoring, and stunting prevention, and effective at strengthening families’ ability to manage, coordinate, and implement child health practices related to stunting prevention.The FBN-based educational programme effectively strengthened family stunting prevention behaviours and enhanced families' capacity to support optimal child growth.